Evaluasi Pemijahan Induk Ikan Baung (Mystus nemurus) Yang Diberi Pakan Keong Mas (Pomacea canaliculata) - Bakti, Alfito Ramanda; Verdian, Aldi Huda; Faturrohman, Kurnia; Mujiono, Mujiono (Universitas Mataram, 2025)
This study aims to evaluate the effects of feeding golden apple snails (Pomacea canaliculata) on the growth and gonad development of prospective broodstock of Asian Redtail Catfish (Mystus nemurus). The background of the research is based on the declining population of Asian Redtail Catfish in the wild due to overexploitation, necessitating effective aquaculture efforts with attention to broodstock nutrition. Golden apple snails were chosen as an alternative feed due to their high protein and nutrient content, as well as their abundant availability and cost-effectiveness. The research method was experimental, comparing two treatment groups: the first group was fed golden apple snails, and the second group was given commercial pellets as a control. The observed parameters included egg diameter, fecundity, fertilization rate (FR), hatching rate (HR), survival rate (SR), and water quality. The fish were reared for three months in aquaculture ponds with periodic water quality monitoring. The results showed that feeding golden apple snails had a significantly positive impact on the reproductive performance of Asian Redtail Catfish. The snail-fed group exhibited higher fecundity (averaging 130,678 eggs) compared to the pellet-fed group (91,025 eggs). Additionally, the snail-fed group had superior FR (92%), HR (87%), and SR (79%) compared to the pellet-fed group (FR 88%, HR 81%, SR 76%). The egg diameter from snail-fed broodstock was larger (2.01 ± 0.14 mm) than that of the pellet-fed group (1.61 ± 0.04 mm), indicating better egg quality. Based on these findings, it was concluded that golden apple snails are effective as an alternative feed for enhancing the reproductive productivity of Asian Redtail Catfish. The nutrients in the snails, particularly protein, fats, and essential amino acids, play a crucial role in supporting gonad development and egg quality. This study recommends the use of golden apple snails in Asian Redtail Catfish aquaculture, with the suggestion that further research be conducted to determine the optimal dosage and feeding strategy. The implementation of these findings is expected to support sustainable Asian Redtail Catfish farming and improve the availability of high-quality fry.